Effect of 2000-meter rowing test on parameters of intestinal integrity in elite rowers during competitive phase - observational study - Dziewiecka, H.; Ostapiuk-Karolczuk, J.; Kasperska, A.; Cichon, J.; Basta, P.; Skarpanska-Stejnborn, A. (Research Square, 2024)
The epithelial wall leakage has been extensively studied in sports disciplines like running and cycling. However, little is known about gut permeability in other disciplines, like rowing, especially after the regular competition performance distance of 2000 meters. Therefore, our study aimed to check gut permeability after the 2000-meter rowing test in the annual training cycle. The study was performed at the beginning of a competitive training phase. Eighteen elite rowers of the Polish Rowing Team participated in study after applying the inclusion/exclusion criteria. The participants performed a 2000-meter ergometer test. Blood samples were taken before the test, after exercise, and after 1-hour of restitution. Parameters, such as I-FABP, LPS, LBP, and zonulin, were determined using appropriate biochemical tests. There were no changes between pre- and post-exercise values in I-FABP, LBP, LPS, and zonulin. However, the I-FABP changed from 6,49 ± 2,15 to 8,3 ± 2,71 (ng/ml) during the recovery period, and LBP decreased from 2,73 ± 0,77 to 2,035 ± 0,53 (µg/ml) simultaneously. Other parameters have not changed. The results of this study showed that intense physical effort performed during the training period is sufficient to negatively affect the gut integrity of rowers.